2010
DOI: 10.1590/s0066-782x2010005000152
|View full text |Cite
|
Sign up to set email alerts
|

Bloqueio simpático esquerdo por videotoracoscopia no tratamento da cardiomiopatia dilatada

Abstract: Background: The level of sympathetic nervous activity is a major determinant of prognosis in patients with heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…29 More recently, within our setting, left sympathetic therapeutic block by means of thoracoscopy in patients with heart failure has shown promising results. 12 The clinical improvement and the better left ventricular function observed in patients undergoing this procedure over the first six months of follow-up have been similar to those documented from using other well established procedures for treating chronic heart failure. Findings from imaging examinations using 123I-metaiodobenzylguanidine have indicated that bilateral upper thoracic sympathectomy mildly suppresses the activation of the sympathetic nerve system, like in beta-blocker therapy.…”
Section: -19supporting
confidence: 72%
“…29 More recently, within our setting, left sympathetic therapeutic block by means of thoracoscopy in patients with heart failure has shown promising results. 12 The clinical improvement and the better left ventricular function observed in patients undergoing this procedure over the first six months of follow-up have been similar to those documented from using other well established procedures for treating chronic heart failure. Findings from imaging examinations using 123I-metaiodobenzylguanidine have indicated that bilateral upper thoracic sympathectomy mildly suppresses the activation of the sympathetic nerve system, like in beta-blocker therapy.…”
Section: -19supporting
confidence: 72%
“…The results suggest a difference between the two groups regarding improvement in the functional class. The patients undergoing sympathectomy showed a statistically significant improvement in the six-minute walk test and the quality of life questionnaire (12,13).…”
mentioning
confidence: 95%
“…[ 1 2 ] It has become the primary surgical procedure opted for sympathectomy in primary hyperhidrosis cases through its superiorities. [ 2 3 ]…”
mentioning
confidence: 99%